Characterization and Evaluation of Aerobic Rice Genotypes under Transplanted Condition - Akter, S; Pervin, S; Iftekharuddaula, KM; Akter, A; Yasmeen, R (Bangladesh Rice Journal, 2016)
Due to over sinking of underground water, scarcity of irrigation water is becoming a threat to the sustainability of irrigated rice production and the concept of aerobic culture appeared prominently. Aerobic rice has the ability to grow under minimum irrigation water and minimum yield reduction occurs when grown under aerobic culture with less water. This experiment aimed to evaluate two advanced aerobic rice lines under transplanted condition in net house. Two advanced lines, IR83140-B-36-B-B and IR83142-B-71-B-B and two check varieties BRRI dhan28 and BRRI dhan29 were grown in three moisture regimes. The moisture regimes included a) continuous standing water (CSW) b) saturated moisture condition (SMC) and c) moisture content at field capacity (FCM). The experimental units, drum containing 110 kg soil, were arranged in randomized complete block design (RCBD) with five replications. Three to four seedlings of forty days were transplanted at the soil surface of each drum. Seedlings were thinned to one plant per genotypes one week after transplanting. Genotype × water interaction showed significant variation in total dry matter production, panicle length, panicle exertion rate, sterility percentage and yield contributing characters. Irrespective of the genotypes, CSW conditions favored to produce maximum number of tiller and panicle. Although BRRI dhan29 gave the highest yield at both CSW and SMC, IR83142-B-71-B-B produced the highest yield at FCM. However, BRRI dhan28 gave similar yield to that of IR83142-B-71-B-B in FCM treated drums. Bangladesh Rice j. 2016, 20(1): 45-50